Thermoluminescence of AMOLED substrate glasses in recent mobile phones for retrospective dosimetry. (March 2019) - Kim, Hyoungtaek; Kim, Min Chae; Lee, Jungil; Chang, Insu; Lee, Seung Kyu; Kim, Jang-Lyul
Abstract: Forty mobile phones using active-matrix organic light-emitting diode (AMOLED) display glasses were tested as emergency dosimeters. The target material was a substrate glass for AMOLED layers located under a cover glass. The measured thermoluminescence (TL) emission spectra and glow curves showed that the glasses are all included in category A and B of a previous study, and the ratio between category A and B was about 8 to 2 for all measured samples. A pre-bleach was applied for 500 s, and TL signals were acquired by measuring the whole wavelength region by removing a UV filter (U-340). This was possible in the same measurement sequence by modifying the Risø TL/OSL DA-20 reader in such a way, that the LED module, used for pre-bleaching, is separated from the detector unit, used for the TL measurement. The signal increase after removing the filter was approximately 50 and 90 times for category A and B, respectively. The zero dose distribution with an average of 34 mGy and a minimal detectable dose (3σ) of 90 mGy was recorded for the forty mobile phones. The position distribution of zero doses across the entire substrate glass of a phone showed a standard deviation of more than 60% for three phone samples. Linear dose response from 30 mGy to 10 Gy was observed, and fading data of the TL signal from glass samples of 22 mobile phones assessed, for up to twenty days after irradiation. Highlights: AMOLED substrate glasses showed favorable dosimetric properties. A TL reader was modified to allow a bleach and TL reading without filter in a single sequence. Category A and B glasses were compared in the same measurement setup.